Some leptothecate hydroids (Cnidaria, Hydrozoa) from Hawaii, mostly from inshore and nearshore waters - Calder, Dale R. (Zootaxa, 2020)
This report is based on a small collection of hydroids from the Hawaiian Islands, in the central Pacific Ocean. Most of the examined material was obtained by staff of the Bernice Pauahi Bishop Museum, Honolulu, during surveys for nonindigenous marine species in shallow, sheltered, inshore or nearshore waters, and especially in harbours, bays, and lagoons. In all, 34 species of leptothecate hydroids, assigned to 14 families and 20 genera, were identified and are discussed. One of them, based on a single infertile colony with a damaged hydrotheca, was identified provisionally only to the rank of suborder. Given the limited geographic and bathymetric focus of the surveys, only four of the species, Clytia thornelyi, Halecium sibogae, Macrorhynchia balei, and M. hawaiensis, were collected at depths greater than 25 m. Seven species, Cirrholovenia tetranema Kramp, 1959, Orthopyxis crenata (Hartlaub, 1901), Clytia elongata Marktanner-Turneretscher, 1890, C. paulensis (Vanhöffen, 1910), Tridentata maldivensis (Borradaile, 1905), Monotheca flexuosa (Bale, 1894), and a hydroid identified only as Eirenida (undetermined), are recorded from Hawaii for the first time. Three others, Lytocarpia nigra (Nutting, 1905) Macrorhynchia balei (Nutting, 1905), and M. hawaiensis (Nutting, 1905), have their type localities in Hawaii, with the last of these being known to date only from the Hawaiian archipelago. Most of the species are well-known from shallow water areas across the tropical and subtropical Indo-Pacific region, and over half of them have been reported as well from warm waters in the Atlantic Ocean. Their existence in the remote islands of Hawaii is attributed to long-range dispersal by both natural and human-mediated means, including shipping.